1990
DOI: 10.1080/00207219008921226
|View full text |Cite
|
Sign up to set email alerts
|

Impedance calculations for modified coplanar waveguides

Abstract: In view of the fact that recessed-gate FETs (Furutsuka et al. 1979) can sustain higher breakdown voltages and hence more power than conventional FETs, it is important to design new microwave transmission lines compatible with recessedgate FETs on GaAs monolithic integrated circuits (MICs). Structures and impedances of three modified coplanar waveguides (CPWs) are presented here: (1) a finite-thickness CPW with a third ground plane for improved heat-sinking, (2) an abrupt-recessed strip CPW, and (3) a graded-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Furthermore, this assumption requires that the gap region that is formed between the conductors (due to their finite thickness) is either filled with the material to be measured (a simple task in the case of liquid and semisolid sample materials) or with an additional material after manufacture (e.g., epoxy resin). Alternatively, the planar lines could be manufactured so that they are embedded in the substrate material, flush with the top face of the substrate [10]. For these situations ε * eff is a linear function of ε * , namely,…”
Section: Determining ε * From γmentioning
confidence: 99%
“…Furthermore, this assumption requires that the gap region that is formed between the conductors (due to their finite thickness) is either filled with the material to be measured (a simple task in the case of liquid and semisolid sample materials) or with an additional material after manufacture (e.g., epoxy resin). Alternatively, the planar lines could be manufactured so that they are embedded in the substrate material, flush with the top face of the substrate [10]. For these situations ε * eff is a linear function of ε * , namely,…”
Section: Determining ε * From γmentioning
confidence: 99%
“…To our knowledge, no closed-form expressions for the effective dielectric constant and the characteristic impedance of the ES-CPW are available. Based on conformal-mapping analysis of the recessed strip CPW in [13], we tried to use conformal mapping to obtain such expressions, but found out that this could be tedious and not really necessary for our air-bridge study, as will be shown below.…”
Section: Equivalent-circuit Modelmentioning
confidence: 99%